Numerical investigation and an effective modelling on the Selective Laser Melting (SLM) process with aluminium alloy 6061 - Loh, Loong-Ee (2018)
The Selective Laser Melting (SLM) fabrication process is complex and it is crucial to understand the phenomena that will occur to better control it. In this paper, an FE model on SLM that considers powder-to-solid transition together with an effective method to achieve volume shrinkage and material removal has been created. Experiments were conducted to validate the model. A detailed discussion on the progression of the melt pool and the rate of temperature change has been made. Parametric study with the laser power and scan speed as variables has been conducted to identify their relationships with the melt dimensions, melting and evaporation of powder and rates of temperature change.